Interventionism in general surgery. Analysis of 150 procedures - Andreoli, Gustavo; Secondo, Gerardo; Kaitazzof, Pedro (Cirugía del Uruguay, 2004)
lmage-guided percutaneous procedures constitute techniques which are currently employed with diagnostic or therapeutic criteria, in a large variety of patho/ogies or clinical situations which the general surgeon encounters in his practice. In this conceptual framework the authors analyse, on the basis of a protoco/ filled in prospective, the first 150 procedures performed in Surgical Clinic "2" of the Maciel Hospital and Surgica/ Oepartament of the Central Armed Forces Hospital in the period from March 1996 through February 2000